2021
DOI: 10.2174/1871524920999201027125743
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, GC-MS Evaluation and Anti-epileptic Potential of Seeds Ethanolic Extract of Putranjiva roxburghii Wall

Abstract: Background: Putranjiva roxburghii Wall is traditionally known to cure many pathological conditions including epilepsy. Objective: The present study is aimed at determining bioactive compounds in ethanolic extract of Putranjiva roxburghii test extract (PRTE) seeds by GCMS analysis and to assess its anti-epileptic potential using various experimental models of epilepsy. Methods: The ethanolic extract of seeds of Putranjiva roxburghiiwas subjected to GC-MS analysis to detect the bioactive phytoconstituents. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“… 192 More recent studies have revealed the anti-BC, anti-epileptic, antioxidant, anti-inflammatory, antimicrobial, anti-nociceptive and anti-pyretic potentials of P. roxburghii leaf and seed extracts. 193–195 However, further mechanistic studies are required to explain how P. roxburghii extracts exert these pharmacological activities.…”
Section: The Anti-breast Cancer Mechanisms Of Medicinal Plant Extracts/essential Oils and Anti-breast Cancer Activities Of Their Nanoformmentioning
confidence: 99%
“… 192 More recent studies have revealed the anti-BC, anti-epileptic, antioxidant, anti-inflammatory, antimicrobial, anti-nociceptive and anti-pyretic potentials of P. roxburghii leaf and seed extracts. 193–195 However, further mechanistic studies are required to explain how P. roxburghii extracts exert these pharmacological activities.…”
Section: The Anti-breast Cancer Mechanisms Of Medicinal Plant Extracts/essential Oils and Anti-breast Cancer Activities Of Their Nanoformmentioning
confidence: 99%
“…Besides the well-known trapping of (hetero)cyclic carbenes with sulfur, the transformation of di-or trihalogenated compounds to halocarbenes and the following reaction with sulfur are considered as a convenient process [49][50][51]. Common halogenated reagents are chloroform (6), trimethyl(trifluoromethyl)silane (F3CSiMe3, 7) and the sodium oxides leads to many by-products, rendering this approach less attractive [31]. The reaction of isocyanides with disulfides in the presence of thallium (I)-salts as catalysts also leads to the formation of ITCs [32].…”
Section: Synthesis Of Itcs Through Thiocarbonyl Surrogatesmentioning
confidence: 99%
“…Besides the well-known trapping of (hetero)cyclic carbenes with sulfur, the transformation of di-or trihalogenated compounds to halocarbenes and the following reaction with sulfur are considered as a convenient process [49][50][51]. Common halogenated reagents are chloroform (6), trimethyl(trifluoromethyl)silane (F 3 CSiMe 3 , 7) and the sodium and potassium salts of chlorodifluoroacetic acid (e.g., ClF 2 CCO 2 Na, 8) and bromodifluoroacetic acid (e.g., BrF 2 CCO 2 K, 9, Scheme 3) [52]. Notably, (triphenylphosphonio)difluoroacetate (PDFA, 10), prepared from BrF 2 CCO 2 K with triphenylphosphine, is a more efficient precursor of difluorocarbene based on the research work of Xiao and co-workers [53,54].…”
Section: Synthesis Of Itcs Through Thiocarbonyl Surrogatesmentioning
confidence: 99%
See 1 more Smart Citation